Fin-de-Siècle Fictions, 1890s-1990s Apocalypse, Technoscience, Empire - Mousoutzanis, A. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Fin-de-Siècle Fictions, 1890s- 1990s focuses on fin-de-siècle British and postmodern American fictions of apocalypse and investigates the ways in which these narratives demonstrate shifts in the relations among modern discourses of power and knowledge.